(3aJM GdCHhGH Hjf Phj GdCdHGH hHjf QH GdCQHGHs - (3Ydj Hf ehSi Hf LYaQ Hf eMeO Hf eMeO Hf GdWGhSs ((3GdfLa s)
(3ChdgG (B:s
(3jbhd GdWGhS CMeO Gddg Ld LdGdg GdPj YWa Ydi ChdjGFg hNGUJg hdWa dge HeG CQGge s
(3BNQgG (B:s
"(3aHTQ YHGOj GdPjf jSJYehf Gdbhd ajJHYhf CMSfg(B" (3hgPG BNQ eG CQOfG PcQg aj gPG GdHGH s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B158s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(997) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs